Comparison of costs of brick construction and concrete structure based on functional units - Sazedj, Soheyl (2013)
In the context of economic sustainability of building construction, it is an issue to decide which constructive solution is more reasonable without loosing quality. This study is about the comparison of the costs of construction of structural walls; conventional reticulated reinforced concrete structure filled with ceramic blocks versus unreinforced masonry with ceramic blocks. Functional units are defined as inner and outer walls to enable a further specification of the costs in order to perform a more detailed comparison without having designed a specific architecture. The results show a lower cost of unreinforced masonry construction, especially in the case of small buildings, whether for home or public services.